Analisis Ergonomi Fasilitas Pintu Kelas Fakultas Teknik Universitas X - Nabila Shafira Dewi; Pramestari, Diah (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
The effectiveness of the educational process, comfort, and safety are all greatly enhancedby an ergonomic learning environment. The layout of classroom facilities, which includesdoors as the main access and departure points, is one area that needs consideration. Thisstudy uses student anthropometrics and ergonomic principles to examine the ergonomicsof classroom doors on the eighth floor of University X's Faculty of Engineering.Students enrolled in an industrial ergonomics course were directly measured aspart of the quantitative research methodology. Height, shoulder breadth, standingelbow height, handgrip diameter, and maximum thumb-to-pinky finger width wereamong the anthropometric measurements that were gathered. The optimal doordimensions—height, width, handle height, handle diameter, and handle length—were then determined by analyzing the student's anthropometric dataThe findings demonstrated that the only door handle diameter that was both ergonomicand in line with the anthropometric measurements of the students was 5 cm. At 216 cm, thedoor height goes above the ideal size of 199.4 cm; at 80 cm, the door width falls short ofthe ideal size of 103.3 cm; at 116 cm, the handle height goes above the ideal size of 106.8cm; and at 11 cm, the handle length falls short of the ideal size of 15.5 cm.Discomfort and an increased risk of musculoskeletal problems could result from thesedimensional differences. As a consequence, the study suggests changing the design ofclassroom doors to make them more user-friendly, secure, and ergonomic.